Additive for optimizing performance of ferroelectric film material and method for optimizing energy storage performance of sodium bismuth titanate-based ferroelectric film
By using optimized additives and specific process steps, preparing sodium titanate base iron electrocomputer film to solve the problem of small total energy storage of thin film capacitors, and significantly improves its polarization and energy storage performance.
Patent Information
- Application Number
- CN202411487625.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-24
- Publication Date
- 2025-01-28
Smart Images

Figure CN119371231A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of electronic functional materials and devices, and in particular to an additive for optimizing the performance of a ferroelectric thin film material and a method for optimizing the energy storage performance of a sodium bismuth titanate-based ferroelectric thin film. Background Art
[0002] With the popularization of modern power systems and the development of electronic products, including new energy power generation and grid connection, the application and promotion of new energy vehicles, the miniaturization and lightweight of portable electronic devices, etc., these fields are inseparable from the development of capacitors. Dielectric capacitors have the advantages of high power density and fast charging and discharging speed, especially film capacitors with small size and high energy density. As one of the three major capacitors, film capacitors also have the advantages of high breakdown strength, low energy loss and good working stability. However, due to its small size, the total energy storage of film capacitors is small, which in turn limits the widespread application of film capacitors. Therefore, further optimizing the energy storage density of film capacitors has important application value and is the only way for the development of modern electrical systems. Summary of the invention
[0003] The purpose of the present invention is to provide an additive for optimizing the performance of ferroelectric thin film materials and a method for optimizing the energy storage performance of sodium bismuth titanate-based ferroelectric thin films, so as to solve the above technical problems.
[0004] In order to achieve the above-mentioned object of the invention, the present invention provides the following technical solutions:
[0005] The present invention provides an additive for optimizing the performance of ferroelectric thin film materials, comprising the following components:
[0006] N,N-dimethylacetamide, ethanolamine, lactic acid, ethylene glycol methyl ether, and propionic acid;
[0007] The volume ratio of the N,N-dimethylacetamide, ethanolamine, lactic acid, ethylene glycol methyl ether and propionic acid is 1-3:4-12:3-5:1-2:1-2.
[0008] The present invention also provides a method for optimizing the energy storage performance of sodium bismuth titanate-based ferroelectric thin films, comprising the following steps:
[0009] 1) adding acetylacetone, tetrabutyl titanate and water to a mixed solution of bismuth nitrate, sodium acetate and acetic acid in sequence according to a stoichiometric ratio to obtain a solution A;
[0010] 2) adding bismuth nitrate, magnesium acetate and zirconium n-propoxide to acetic acid in sequence according to a stoichiometric ratio to obtain a solution B;
[0011] 3) mixing solution A, solution B and the additive according to claim 1 and aging the mixture to obtain a precursor solution;
[0012] 4) Spin coating the precursor solution on a substrate, followed by drying, pyrolysis and annealing to obtain a sodium bismuth titanate-based ferroelectric thin film;
[0013] 5) Repeat step 4) until the target thickness is reached.
[0014] Furthermore, the chemical composition of the sodium bismuth titanate-based ferroelectric film is: 0.6 (Na 0.5 Bi 0.5 )TiO 3 -0.4Bi(Mg 0.5 Zr 0.5 ) 3 .
[0015] Furthermore, the volume ratio of the acetic acid, acetylacetone and deionized water is 12-20:1-3:2-4.
[0016] Furthermore, the dosage of the additive is 1 to 1.5 mL of the additive per 10 mL of the precursor solution.
[0017] Further, the concentration of the precursor solution is 0.15-0.3 mol / L;
[0018] The aging time is 2 to 10 days.
[0019] Furthermore, the spin coating speed is 2500-4500 r / min, and the spin coating time is 30-40 s;
[0020] The drying temperature is 200-250° C., and the drying time is 3-5 minutes.
[0021] Furthermore, the pyrolysis is divided into two stages: the first stage is pyrolysis at 400-450°C for 5-10 minutes, and the second stage is heat preservation at 700-750°C for 3-8 minutes.
[0022] Furthermore, the annealing temperature is 700-750° C., and the annealing time is 10-15 min.
[0023] Furthermore, the thickness of the sodium bismuth titanate-based ferroelectric film is 500-700 nm.
[0024] Beneficial effects of the present invention:
[0025] The present invention compares two kinds of 0.6 (Na 0.5 Bi 0.5 )TiO 3 -0.4Bi(Mg 0.5 Zr 0.5 ) 3Ferroelectric thin film, proved that the addition of additives can significantly improve the polarization performance and energy storage performance. Under the electric field of 2000kV / cm, the maximum polarization increased from 63.56μC / cm 2 Increased to 109.48μC / cm 2 , increased by about 70%, and the energy storage performance increased from 44.38J / cm 3 Increased to 60.92J / cm 3 , an increase of about 40%. BRIEF DESCRIPTION OF THE DRAWINGS
[0026] Figure 1 0.6(Na 0.5 Bi 0.5 )TiO 3 -0.4Bi(Mg 0.5 Zr 0.5 ) 3 Schematic diagram of the structure of a ferroelectric thin film microcapacitor made of ferroelectric thin film material;
[0027] Figure 2 0.6 (Na 0.5 Bi 0.5 )TiO 3 -0.4Bi(Mg 0.5 Zr 0.5 ) 3 XRD patterns of ferroelectric thin film materials;
[0028] Figure 3 0.6 (Na 0.5 Bi 0.5 )TiO 3 -0.4Bi(Mg 0.5 Zr 0.5 ) 3 Surface scan of ferroelectric thin film material;
[0029] Figure 4 0.6 (Na 0.5 Bi 0.5 )TiO 3 -0.4Bi(Mg 0.5 Zr 0.5 ) 3 Hysteresis loop diagram of ferroelectric thin film materials;
[0030] Figure 5 0.6 (Na 0.5 Bi 0.5 )TiO 3 -0.4Bi(Mg 0.5 Zr0.5 ) 3 Comparison of energy storage performance and efficiency of ferroelectric thin film materials. DETAILED DESCRIPTION
[0031] The present invention provides an additive for optimizing the performance of ferroelectric thin film materials, comprising the following components:
[0032] N,N-dimethylacetamide, ethanolamine, lactic acid, ethylene glycol methyl ether, and propionic acid;
[0033] The volume ratio of the N,N-dimethylacetamide, ethanolamine, lactic acid, ethylene glycol methyl ether and propionic acid is 1-3:4-12:3-5:1-2:1-2.
[0034] In the present invention, the volume ratio of N,N-dimethylacetamide, ethanolamine, lactic acid, ethylene glycol methyl ether and propionic acid is preferably 1.5-2.5:5-10:3.5-4.5:1.2-1.8:1.2-1.8, and more preferably 2:6-8:4:1.5:1.5.
[0035] The present invention also provides a method for optimizing the energy storage performance of sodium bismuth titanate-based ferroelectric thin films, comprising the following steps:
[0036] 1) adding acetylacetone, tetrabutyl titanate and water to a mixed solution of bismuth nitrate, sodium acetate and acetic acid in sequence according to a stoichiometric ratio to obtain a solution A;
[0037] 2) adding bismuth nitrate, magnesium acetate and zirconium n-propoxide to acetic acid in sequence according to a stoichiometric ratio to obtain a solution B;
[0038] 3) mixing solution A, solution B and the additive according to claim 1 and aging the mixture to obtain a precursor solution;
[0039] 4) Spin coating the precursor solution on a substrate, followed by drying, pyrolysis and annealing to obtain a sodium bismuth titanate-based ferroelectric thin film;
[0040] 5) Repeat step 4) until the target thickness is reached.
[0041] In the present invention, the chemical composition of the sodium bismuth titanate-based ferroelectric film is: 0.6 (Na 0.5 Bi 0.5 )TiO 3 -0.4Bi(Mg 0.5 Zr 0.5 ) 3 .
[0042] In the present invention, the volume ratio of the acetic acid, acetylacetone and deionized water is 12-20:1-3:2-4, preferably 13-14:1.5-2.5:2.5-3.5, and more preferably 13.5-13.8:1.8-2.0:3.0-3.2.
[0043] In the present invention, in step 1), the mixing temperature of bismuth nitrate, sodium acetate and acetic acid is 80-110° C., preferably 90-100° C., and more preferably 95° C.; the mixing time is 20-40 min, and preferably 30 min.
[0044] In the present invention, in step 2), the mixing temperature of bismuth nitrate and acetic acid is 80-110° C., preferably 90-100° C., and more preferably 95° C.; the mixing time is 20-40 min, and preferably 30 min.
[0045] In the present invention, the dosage of the additive is 1-1.5 mL of the additive per 10 mL of the precursor solution, preferably 1.2-1.4 mL, and more preferably 1.3 mL.
[0046] In the present invention, the concentration of the precursor solution is 0.15 to 0.3 mol / L, preferably 0.18 to 0.25 mol / L, and more preferably 0.20 to 0.22 mol / L.
[0047] In the present invention, the aging time is 2 to 10 days, preferably 3 to 9 days, and more preferably 4 to 6 days.
[0048] In the present invention, the spin coating speed is 2500-4500 r / min, preferably 3000-4000 r / min, and more preferably 3500 r / min; the spin coating time is 30-40 s, preferably 32-38 s, and more preferably 35 s.
[0049] In the present invention, the drying temperature is 200-250° C., preferably 210-240° C., and more preferably 220-230° C.; the drying time is 3-5 min, and preferably 4 min.
[0050] In the present invention, the pyrolysis is divided into two stages: the first stage is pyrolysis at 400-450°C for 5-10 min, preferably pyrolysis at 420°C for 8 min; the second stage is heat preservation at 700-750°C for 3-8 min, preferably heat preservation at 720°C for 5 min.
[0051] In the present invention, the annealing temperature is 700-750° C., preferably 710-740° C., and more preferably 720-730° C.; the annealing time is 10-15 min, preferably 11-14 min, and more preferably 12-13 min.
[0052] In the present invention, the thickness of the sodium bismuth titanate-based ferroelectric thin film is 500-700 nm, preferably 550-650 nm, and more preferably 580-620 nm.
[0053] The technical solutions provided by the present invention are described in detail below in conjunction with the embodiments, but they should not be construed as limiting the protection scope of the present invention.
[0054] Example 1
[0055] (1) 3 mL of N,N-dimethylacetamide, 4 mL of ethanolamine, 5 mL of lactic acid, 2 mL of ethylene glycol methyl ether, and 2 mL of propionic acid were measured in a volume ratio of 3:4:5:2:2, mixed and stirred for 30 minutes to obtain an additive;
[0056] (2) Solution A preparation: Measure 18 mL of acetic acid and prepare a solution according to the molecular formula Bi 0.5 Na 0.5 TiO 3 Weigh bismuth nitrate pentahydrate: sodium acetate trihydrate: tetrabutyl titanate in a molar ratio of 1:1:2; 3 O 9 ·5H 2 O (purity 99%) and 0.3629 g CH 3 COONa·3H 2 O (purity of 99%) was mixed in acetic acid and stirred in a water bath at 100°C for 30 minutes; after cooling, 2.4 mL of acetylacetone was added and stirred for 20 minutes; 1.6504 g of tetrabutyl titanate (purity of 98%) was added and stirred at room temperature for 30 minutes; then 2.5 mL of deionized water was added and stirred for 10 minutes to obtain solution A;
[0057] (3) Solution B preparation: Measure 18 mL of acetic acid and prepare a solution according to the molecular formula BiMg 0.5 Zr 0.5 O 3 Weigh bismuth nitrate pentahydrate: magnesium acetate tetrahydrate: zirconium n-propoxide in a molar ratio of 2:1:1; 3 O 9 ·5H 2 O (purity 99%) and 0.3431 g of C 4 H 6 MgO 4 ·4H 2O (purity 99%) was mixed in acetic acid and stirred in a water bath at 100°C for 20 min; after cooling, zirconium n-propoxide was added and stirred at room temperature for 10 min to obtain solution B;
[0058] (4) Solution A and Solution B were mixed and stirred at room temperature for 60 min, then 4 mL of additive was added, stirred at room temperature for 6 h, and then aged for 5 days to obtain 0.6 (Na 0.5 Bi 0.5 )TiO 3 -0.4Bi(Mg 0.5 Zr 0.5 ) 3 Precursor solution;
[0059] (5) Place the clean and dry Si / Pt substrate on the spin coater and press the adsorption button; 0.5 Bi 0.5 )TiO 3 -0.4Bi(Mg 0.5 Zr 0.5 ) 3 The precursor solution was dripped onto the Pt / Si substrate, the spin coating speed was set to 3000 r / min, and the spin coating time was controlled at 30 s; the obtained wet film was transferred to a glue dryer and dried at 200 °C for 4 min; the dried glue film was transferred to a rapid annealing furnace, pyrolyzed at 400 °C for 8 min, and kept at 700 °C for 4 min;
[0060] (6) Repeat step (5) 10 times, place the film in a tube furnace and keep it at 700°C for 10 min.
[0061] Example 2
[0062] The difference from Example 1 is that 2 mL of N,N-dimethylacetamide, 8 mL of ethanolamine, 3 mL of lactic acid, 1.5 mL of ethylene glycol methyl ether and 1.5 mL of propionic acid are measured in a volume ratio of 2:8:3:1.5:1.5, mixed and stirred for 30 minutes to obtain an additive.
[0063] Example 3
[0064] The difference from Example 1 is that 1 mL of N,N-dimethylacetamide, 12 mL of ethanolamine, 3 mL of lactic acid, 1 mL of ethylene glycol methyl ether and 1 mL of propionic acid are measured in a volume ratio of 1:12:3:1:1, mixed and stirred for 30 minutes to obtain an additive.
[0065] Comparative Example 1
[0066] (1) Solution A preparation: Measure 18 mL of acetic acid and prepare a solution according to the molecular formula Bi 0.5 Na 0.5 TiO 3Weigh bismuth nitrate pentahydrate: sodium acetate trihydrate: tetrabutyl titanate in a molar ratio of 1:1:2; 3 O 9 ·5H 2 O (purity 99%) and 0.3629 g CH 3 COONa·3H 2 O (purity of 99%) was mixed in acetic acid and stirred in a water bath at 100°C for 30 minutes; after cooling, 2.4 mL of acetylacetone was added and stirred for 20 minutes; then 1.6504 g of tetrabutyl titanate (purity of 98%) was added and stirred at room temperature for 30 minutes; then 2.5 mL of deionized water was added and stirred for 10 minutes to obtain solution A;
[0067] (2) Solution B preparation: Measure 18 mL of acetic acid and prepare a solution according to the molecular formula BiMg 0.5 Zr 0.5 O 3 Weigh bismuth nitrate pentahydrate: magnesium acetate tetrahydrate: zirconium n-propoxide in a molar ratio of 2:1:1. 3 O 9 ·5H 2 O (purity 99%) and 0.3431 g of C 4 H 6 MgO 4 ·4H 2 O (purity 99%) was mixed in acetic acid and stirred in a water bath at 100°C for 20 min; after cooling, zirconium n-propoxide was added and stirred at room temperature for 10 min to obtain solution B;
[0068] (3) Solution A was mixed with solution B, 4 mL of acetic acid was added, stirred at room temperature for 60 min, and then aged for 5 days to obtain 0.6 (Na 0.5 Bi 0.5 )TiO 3 -0.4Bi(Mg 0.5 Zr 0.5 ) 3 Precursor solution;
[0069] (4) Place the clean and dry Si / Pt substrate on the spin coater and press the adsorption button; 0.5 Bi 0.5 )TiO 3 -0.4Bi(Mg 0.5 Zr 0.5 ) 3The precursor solution was dripped onto the Si / Pt substrate, the spin coating speed was set to 3000 r / min, and the spin coating time was controlled at 30 s; the obtained wet film was transferred to a glue dryer and dried at 200 °C for 4 min; the dried glue film was transferred to a rapid annealing furnace, pyrolyzed at 400 °C for 8 min, and kept at 750 °C for 4 min;
[0070] (5) Repeat step (4) 10 times, place the film in a tube furnace and keep it at 700°C for 10 min.
[0071] It can be seen from the above embodiments that the present invention provides an additive for optimizing the performance of ferroelectric thin film materials and a method for optimizing the energy storage performance of sodium bismuth titanate-based ferroelectric thin films. Figure 1 For the preparation of 0.6 (Na 0.5 Bi 0.5 )TiO 3 -0.4Bi(Mg 0.5 Zr 0.5 ) 3 Schematic diagram of the structure of a ferroelectric thin film microcapacitor. It can be observed that from bottom to top it is composed of Si, Pt, ferroelectric thin film and Au. Figure 2 It can be seen that the 0.6 (Na 0.5 Bi 0.5 )TiO 3 -0.4Bi(Mg 0.5 Zr 0.5 ) 3 The thin film materials all present a perovskite structure with good crystallinity. Figure 3 It can be seen that the 0.6 (Na 0.5 Bi 0.5 )TiO 3 -0.4Bi(Mg 0.5 Zr 0.5 ) 3 Thin film materials all have small and uniform grains. Figure 4 The 0.6 (Na 0.5 Bi 0.5 )TiO 3 -0.4Bi(Mg 0.5 Zr 0.5 ) 3 Hysteresis loop of the microcapacitor. As shown in the figure, it can be clearly seen from the figure that with the addition of additives 0.6 (Na 0.5 Bi 0.5 )TiO 3 -0.4Bi(Mg 0.5 Zr 0.5 ) 3The polarization strength of the microcapacitors is improved to varying degrees, especially in Example 2, which is increased by 70% to 109.48 μC / cm 2 . Figure 5 It shows that under an electric field strength of 2000 kV / cm, the 0.6 (Na 0.5 Bi 0.5 )TiO 3 -0.4Bi(Mg 0.5 Zr 0.5 ) 3 The energy storage performance of the microcapacitors is compared. The optimization effect of Example 2 is the best, and its energy storage density is increased by 40%, from 44.38 J / cm 3 Increased to 60.92J / cm 3 .
[0072] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.
Claims
1. An additive for optimizing the performance of ferroelectric thin film materials, characterized in that: Contains the following ingredients: N,N-dimethylacetamide, ethanolamine, lactic acid, ethylene glycol methyl ether, and propionic acid; The volume ratio of the N,N-dimethylacetamide, ethanolamine, lactic acid, ethylene glycol methyl ether and propionic acid is 1-3:4-12:3-5:1-2:1-2.
2. A method for optimizing the energy storage performance of sodium bismuth titanate-based ferroelectric thin films, characterized in that: The following steps are involved: 1) adding acetylacetone, tetrabutyl titanate and water to a mixed solution of bismuth nitrate, sodium acetate and acetic acid in sequence according to a stoichiometric ratio to obtain a solution A; 2) adding bismuth nitrate, magnesium acetate and zirconium n-propoxide to acetic acid in sequence according to a stoichiometric ratio to obtain a solution B; 3) mixing solution A, solution B and the additive according to claim 1 and aging the mixture to obtain a precursor solution; 4) Spin coating the precursor solution on a substrate, followed by drying, pyrolysis and annealing to obtain a sodium bismuth titanate-based ferroelectric thin film; 5) Repeat step 4) until the target thickness is reached.
3. The method for optimizing the energy storage performance of sodium bismuth titanate-based ferroelectric thin films according to claim 2, characterized in that: The chemical composition of the sodium bismuth titanate-based ferroelectric film is: 0.6 (Na 0.5 Bi 0.5 )TiO3-0.4Bi(Mg 0.5 Zr 0.5 )O3.
4. The method for optimizing the energy storage performance of sodium bismuth titanate-based ferroelectric thin films according to claim 3, characterized in that: The volume ratio of the acetic acid, acetylacetone and deionized water is 12-20:1-3:2-4.
5. The method for optimizing the energy storage performance of sodium bismuth titanate-based ferroelectric thin films according to any one of claims 2 to 4, characterized in that: The dosage of the additive is 1 to 1.5 mL of the additive per 10 mL of the precursor solution.
6. The method for optimizing the energy storage performance of sodium bismuth titanate-based ferroelectric thin films according to claim 5, characterized in that: The concentration of the precursor solution is 0.15-0.3 mol / L; The aging time is 2 to 10 days.
7. The method for optimizing the energy storage performance of sodium bismuth titanate-based ferroelectric thin films according to claim 2 or 6, characterized in that: The spin coating speed is 2500-4500 r / min, and the spin coating time is 30-40 s; The drying temperature is 200-250° C., and the drying time is 3-5 minutes.
8. The method for optimizing the energy storage performance of sodium bismuth titanate-based ferroelectric thin films according to claim 7, characterized in that: The pyrolysis is divided into two stages: the first stage is pyrolysis at 400-450°C for 5-10 minutes, and the second stage is heat preservation at 700-750°C for 3-8 minutes.
9. The method for optimizing the energy storage performance of sodium bismuth titanate-based ferroelectric thin films according to claim 2, 6 or 8, characterized in that: The annealing temperature is 700-750° C., and the annealing time is 10-15 minutes.
10. The method for optimizing the energy storage performance of sodium bismuth titanate-based ferroelectric thin films according to claim 9, characterized in that: The thickness of the sodium bismuth titanate-based ferroelectric film is 500-700 nm.
Citation Information
Cited By
Aurivillius phase ferroelectric film prepared in large area and method and application thereof
CN121108787A